Forensic Handwriting Analysis: Validating the Doc-Scale Approach - Dhillon, Deepika; Kumar Sharma, Bhoopesh; Saroa, Jagjeet Singh; Dhillon, Ishika; Kumari, Ritu (Journal of Neonatal Surgery, 2025)
This study examines the effectiveness of the innovative 'Forensic Doc-Scale' in addressing the limitations of conventional forensic handwriting analysis methods. Handwriting features like slant, alignment, spacing, and dimensions were analyzed in disputed signature cases. Conventional methods often lack precision and are prone to subjectivity, relying on inconsistent tools. The 'Forensic Doc-Scale' introduces standardized features, including proportional grids and alignment markers, to enhance accuracy and objectivity. A comparison with conventional methods using prepared and real forensic cases demonstrated improved precision, reduced subjectivity, and higher reproducibility. Adaptable to various document types, the 'Forensic Doc-Scale' offers significant advantages and is recommended as a standard tool for reliable forensic handwriting analysis